Comparison of Vaginal Versus Cesarean Delivery in Women with Previous Cesarean: A Cross-Sectional Study on Maternal and Neonatal Outcomes - Vishwanath Dange; V. Malathi, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: The decision between attempting a vaginal birth after cesarean (VBAC) and opting for a repeat cesarean delivery (RCD) can significantly impact maternal and neonatal outcomes. This study aims to compare the outcomes associated with these delivery options in women with one previous cesarean. Methods: This cross-sectional study involved 200 women with a history of one previous cesarean section who were delivering at a tertiary care center. Participants were grouped based on their delivery method: vaginal delivery (n=92) or cesarean delivery (n=108). Data were collected on maternal length of hospital stay, neonatal ICU admissions, postpartum hemorrhage, and Apgar scores at 5 minutes. Statistical analyses included t-tests, chi-square, and Fisher's exact tests, as appropriate. Results: The study found that women who underwent vaginal delivery had significantly shorter hospital stays (mean 3.2 ± 1.1 days) compared to those who had a cesarean delivery (mean 4.8 ± 1.4 days; p < 0.001). Neonatal ICU admission rates were lower in the vaginal delivery group (6.5%) compared to the cesarean delivery group (13%; p = 0.045). However, there was no significant difference in the rates of postpartum hemorrhage between the two groups (p = 0.21). Neonates born via vaginal delivery had significantly higher Apgar scores at 5 minutes (mean 9.4 ± 0.6) compared to those born via cesarean delivery (mean 9.1 ± 0.7; p = 0.032) Conclusions: Vaginal delivery in women with a previous cesarean section is associated with shorter hospital stays and potentially better neonatal outcomes in terms of Apgar scores and reduced ICU admissions. These findings support the consideration of VBAC in eligible women but underscore the importance of individualized clinical decision-making based on comprehensive risk assessments.